Capture These Indians for the Lord : Indians, Methodists, and Oklahomans, 1844-1939 - Smith, Tash (Book collections on Project MUSE., 2014)
""Exploring larger issues associated with western expansion, this book details the history of the Southern Methodist Church in Indian Territory/Oklahoma and the complex relationship between its white and Indian membership"--Provided by publisher"--